Neuroprotective effects of 5-aminolevulinic acid against neurodegeneration in rat models of Parkinson's disease and stroke - Masanori Hijioka; Kanori Kitamura; Daijiro Yanagisawa; Kaneyasu Nishimura; Kazuyuki Takata; Masatoshi Inden; Yoshihisa Kitamura (Elsevier, 2020)
Oxidative stress is associated with the progression of the neurodegenerative diseases Parkinson's disease (PD) and cerebral ischemia. Recently, 5-aminolevulinic acid (5-ALA), an intermediate in the porphyrin synthesis pathway, was reported to exert antioxidative effects on macrophages and cardiomyocytes. Here, we demonstrated the neuroprotective effects of 5-ALA using rat models of PD and ischemia as well as in vitro in SH-SY5Y cells. 5-ALA partially prevented neurodegeneration in each condition. These results suggest that 5-ALA has a potential for promising therapeutic agent to protect against neurodegeneration exacerbated by oxidative stress.